The role of interactive gamification through Wordwall Apps to improve students’ engagement and literary comprehension - Najihah Abd Wahid; Farhan; Mualim Wijaya (Asosiasi Relawan dan Pengelola Jurnal LPTNU (ARJUNU), 2025)
This study explores the efficacy of interactive gamification through Wordwall Apps in enhancing literary comprehension and student engagement in educational settings. The aim is to determine whether gamification techniques with Wordwall Apps can significantly improve literary learning outcomes compared to traditional teaching methods. Utilizing a quasi-experimental design, the research involved control and experimental groups from a sample of high school students, where the latter engaged in gamified learning activitie with Wordwall s. The findings reveal that Wordwall gamification markedly increases student engagement and deepens literary comprehension, as evidenced by higher post-test scores in the experimental group compared to the control. These results suggest that interactive gamification not only makes learning more enjoyable but also more effective, encouraging a deeper interaction with literary content.